2009
DOI: 10.1186/1476-7120-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic cardiomyopathy with midventricular obstruction and apical aneurysm formation in a single family: case report

Abstract: BackgroundHypertrophic cardiomyopathy (HCM) is an extremely heterogeneous disease. An under recognized and very often missed subgroup within this broad spectrum concerns patients with left ventricular (LV) apical aneurysms in the absence of coronary artery disease.Case presentationWe describe a case of HCM with midventricular obstruction and apical aneurysm formation in 3 patients coming from a single family. This HCM pattern was detected by 2D-echocardiography and confirmed by cardiac magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
11
1
1
Order By: Relevance
“…9 Identification of identical apical aneurysms in the same family of patients (2 sisters and daughter/nephew) supports the potential role of genetic substrate/predisposition in formation of aneurysms. 10 The present study did not record any significant differences in mid-cavitary gradients between patients with MVO and/or without an apical aneurysm. Taking into consideration the systolic impairment of apex after aneurysm formation, it is reasonable to assume that midventricular gradients must have been higher in the aneurysm group, gradually fading to levels equal to those recorded in patients with MVO but without apical aneurysms.…”
Section: Discussionmentioning
confidence: 55%
“…9 Identification of identical apical aneurysms in the same family of patients (2 sisters and daughter/nephew) supports the potential role of genetic substrate/predisposition in formation of aneurysms. 10 The present study did not record any significant differences in mid-cavitary gradients between patients with MVO and/or without an apical aneurysm. Taking into consideration the systolic impairment of apex after aneurysm formation, it is reasonable to assume that midventricular gradients must have been higher in the aneurysm group, gradually fading to levels equal to those recorded in patients with MVO but without apical aneurysms.…”
Section: Discussionmentioning
confidence: 55%
“…Numerous previous case reports and studies have suggested the existence of overlap between APH, MVO, and APA [8,9,12,13,[16][17][18][19][20][21][22][23]. APH has often been complicated by MVO in previous case reports and studies [9,13,18,20,23].…”
Section: Discussionmentioning
confidence: 95%
“…APA is a rare variant of HCM, in which there is a thin-walled dyskinetic or akinetic segment at the most distal portion of the chamber that has relatively wide communication with the left ventricular cavity [8]. While numerous previous case reports and studies have suggested the existence of considerable overlap between APH, MVO, and APA [8,9,12,13,[16][17][18][19][20][21][22][23], the clinical courses of the above three forms of HCM seem to be heterogeneous. Our previous study and a report by Maron and colleagues have demonstrated a largely unfavorable clinical course for HCM patients with MVO and/or APA [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…HCM is mostly inherited in an autosomal dominant pattern, but modifier genes may also play a role in inheritance patterns and LVA formation. Although the mode of inheritance is unclear, different reports supported the theory of dominant inheritance in HCM patients with LVA and midventricular obstruction …”
Section: Discussionmentioning
confidence: 99%